(untitled) (Al-Farooq Journal of Sciences, 2026)
During the Italian colonial period (1911–1943), Libya witnessed a series of profound economic transformations that affected various productive and service sectors, reshaping the economic structure to align with colonial objectives. The Italian administration sought to redirect the Libyan economy from a traditional economy based on pastoralism and limited agriculture to a dependent one serving the interests of the colonizing state. This was achieved through policies of agricultural settlement, land confiscation, and the introduction of modern production patterns that primarily served Italian settlers. Furthermore, while the colonial authorities developed certain infrastructure—such as roads and ports—these projects were not intended to develop the local economy as much as they were designed to serve military and settlement purposes, as well as to tighten control over resources. These transformations resulted in structural imbalances within the Libyan economy, manifested in the marginalization of the local population, the dismantling of traditional production patterns, and the creation of a clear economic dependence on the colonial center. Accordingly, studying these transformations contributes to understanding the nature of colonial economic policies and their long-term effects on Libyan society, both in terms of reshaping productive relations and cementing economic and social disparities that persisted long after the end of the colonial era.